Broad-Spectrum Foraging, Trade, and Lithic Technology: A First Approach to the Slab Stone Tools from Prehispanic Sierras of Córdoba, Argentina - Sario, Gisela Mariela; Salvatore, Marcos Aníbal; Costantino, Florencia Natalia; Pastor, Sebastián; Medina, Matias Eduardo (Taylor & Francis, 2023)
Fil: Sario, Gisela Mariela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Antropología de Córdoba. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Instituto de Antropología de Córdoba; Argentina